The impact of asymmetric organocatalysis in dearomatization and aromatization of carbocycles: increasing molecular complexity and diversity. Issue 24 (15th June 2016) - Pantaine, Loïc; Moreau, Xavier; Coeffard, Vincent; Greck, Christine
Graphical abstract: Highlights: Combination of organocatalysis with either making or breaking aromaticity is powerful. Dearomatization/organocatalysis enables the preparation of 3D molecules. Chiral polyaromatic architectures are prepared by enantioselective organocatalysis. Abstract: The combination of asymmetric organocatalysis with either making or breaking aromaticity, in a single vessel, has known a rapid development over the last decade. This is due to its success in producing complex molecular architectures efficiently while maintaining a good control over diastereo- and enantioselectivities. This digest will offer a broad summary of the advances in this field, focusing primarily on carbocycles, and will be divided into two main parts: the first will concern combining asymmetric organocatalysis with dearomatization, the second with rearomatization.